Resistance of synthetic hexaploid wheat to the leaf rust pathogen - A. G. Khakimova; E. I. Gultyaeva; O. P. Mitrofanova (Труды по прикладной ботанике, генетике и селекции)
Background. One of the promising sources for enrichment of the common wheat (Triticum aestivum L.) gene pool with new alleles is synthetic hexaploid wheat (SHW), or allopolyploids from crossing tetraploid wheats (2n = 4x = 28, BBAA) with accessions of Aegilops tauschii Coss. (2n = 2x = 14, DD), and subsequent doubling of the chromosome number in the hybrids. Objectives of the study were to evaluate the SHW accessions from the VIR collection for resistance to Puccinia triticina Erikss. populations collected in Russia; genotype the accessions; and summarize information from the published sources concerning the resistance of the studied accessions to other harmful diseases and pests.Materials and methods. Resistance of 36 SHW accessions from the VIR collection to the populations of P. triticina was assessed in the laboratory and in the field, under artificial infection pressure, using the techniques developed by the Institute of Plant Protection. A phytopathological test and PCR markers were used to identify the Lr genes.Results and conclusion. The SHW accessions were characterized according to their resistance to the Russian populations of the wheat leaf rust pathogen. The sources of resistance in the phase of emergence and in adult plants were identified. The phytopathological test isolated three accessions with Lr23; the PCR marker of Lr21=Lr40 was found in 11 accessions, Lr39=Lr41 in 19, and Lr22a in 3. At the same time, k-65496, k-65515 and k-65517 had si multaneously Lr21=Lr40 and Lr39=Lr41, while k-65497, k-65503 and k-65508 had Lr22a and Lr39=Lr41. The analysis of published data showed that many of the studied SHW accessions were also resistant to other harmful diseases and insect pests, so they are of interest for further studying and possible use in domestic breeding.